POTENSI WISATA ALAM DI DESA MAPANE TAMBU KECAMATAN BALAESANG KABUPATEN DONGGALA - Lestari, Dwi; Rukmi, Rukmi (Universitas Tadulako, 2020)
The potential of natural tourism is one of the attractions that can be developed into tourist destinations, natural attaractions include accessibility, accommodation, facilities and inflastructure. Each tourist area has different potential. The purpose of this study was to determine the Â tourism potential in Mapane Tambu Village, Balaesang District, Donggala Regency. This research was conducted in Mapane Tambu Village Balaesang District, Donggala Regency, for two months, from june to july 2019. The method used in this research was descriptive qualitative by describing the uniqueness of natural resources, prominent natural resources. Nature tourism activities carried out, cleanliness of the location of attractions, regional security and comfort in addittion to that interview were conducted as many as 31 respondents. Analysis of the data used is the analysis of the Regional Operation Objects and Attractions of Nature Tourism (AD0-ODTWA) Dirjen PHKA 2003 according to the values that have been determined for each criterion. Based on the results of reseacrh in the village of Mapane Tambu, District of Balaesang, Dist rict of Donggala, the potential of natural tourism possessed by Mapane Tambu Village namely waterfalls, rivers, hot springs, flora and fauna deserve to be developed as natural attractions. The potential of natural tourism in Mapane Tambu Village is feasible to be developed with a feassibility index percentage of 69,58%. The natural tourism area in Mapane Tambu Village has the attraction, accessibility, and supporting facilites and infrastructure so that it is feasible to be developed.Â